2002
DOI: 10.1073/pnas.252469399
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of HIV-1 to entry inhibitors correlates with envelope/coreceptor affinity, receptor density, and fusion kinetics

Abstract: HIV entry inhibitors include coreceptor antagonists and the fusion inhibitor T-20. T-20 binds the first helical region (HR1) in the gp41subunit of the viral envelope (Env) protein and prevents conformational changes required for membrane fusion. HR1 appears to become accessible to T-20 after Env binds CD4, whereas coreceptor binding is thought to induce the final conformational changes that lead to membrane fusion. Thus, T-20 binds to a structural intermediate of the fusion process. Primary viruses exhibit con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
418
5
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 372 publications
(455 citation statements)
references
References 36 publications
30
418
5
2
Order By: Relevance
“…However, we along with others have shown that baseline susceptibility to ENF is quite variable among viruses from different patients (9,20,39), and variations in domains of Env other than HR1 are thought to account for these differences in baseline susceptibility (8,15,34). In particular, susceptibility to fusion inhibitors appears to be dependent on the affinity of gp120 for the coreceptors as well as on coreceptor density at the cell surface, both of which factors affect fusion kinetics (34). A faster fusion process will reduce the length of time during which the ENF molecular target is exposed, thus reducing the virus sensitivity to this inhibitor (28,30,34).…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…However, we along with others have shown that baseline susceptibility to ENF is quite variable among viruses from different patients (9,20,39), and variations in domains of Env other than HR1 are thought to account for these differences in baseline susceptibility (8,15,34). In particular, susceptibility to fusion inhibitors appears to be dependent on the affinity of gp120 for the coreceptors as well as on coreceptor density at the cell surface, both of which factors affect fusion kinetics (34). A faster fusion process will reduce the length of time during which the ENF molecular target is exposed, thus reducing the virus sensitivity to this inhibitor (28,30,34).…”
mentioning
confidence: 63%
“…It is noteworthy, however, that in cases where ENF resistance mutations produced only suboptimal resistance, Env replicative capacity was usually maintained, suggesting that the impact of resistance mutations on viral resistance and viral fitness was not tightly linked (see below). The identification of viral sequences that determine whether a given context is favorable or unfavorable for the expression of high resistance by ENF resistance mutations may prove to be a difficult task, given that multiple discontinuous envelope domains participate in the entry process and can modulate phenotypic resistance to ENF (8,15,34).…”
Section: Vol 80 2006 Evolution Of Hiv-1 Resistance To Enf 8813mentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the mechanisms of membrane fusion, both continuities should be followed and the temporal order in which they occur identified. In the case of the HIV-1 fusion protein Env, mechanistic studies have largely relied on fusion of cells expressing the protein to cells expressing CD4 and cognate chemokine receptors (e.g., Munoz-Barroso et al, 1998;Melikyan et al, 2000;Reeves et al, 2002;Abrahamyan et al, 2003;Gallo et al, 2003;Markosyan et al, 2003). But monitoring lipid dye spread in HIV-1 Env-mediated cell-cell fusion has not proved to be very useful in following membrane continuity, for several reasons.…”
mentioning
confidence: 99%
“…By examining fusion kinetics of various HIV strains we found that the sensitivity of HIV to entry inhibitors correlates with envelope:coreceptor affinity, receptor density and fusion kinetics [25]. The kinetic studies allowed us to determine parameters that govern fusion and inhibition.…”
Section: Protein Intermediates In Membrane Fusionmentioning
confidence: 99%